(untitled) (Ryan Holiday, 2017)
Trust Me, I’m Lying was the first book to blow the lid off the speed and force at which rumors travel online—and get "traded up" the media ecosystem until they become real headlines and generate real responses in the real world.
Keywords: Digital communications,Truyền thông kỹ thuật số; Social aspects,Khía cạnh xã hội